Pembelajaran Tuntas Kitab Kuning Di Pondok Pesantren Ibnu Amin Pamangkih (Tinjauan Metode Dan Evaluasi) - M. Junaidi (STIT Syekh Muhammad Nafis Tabalong, 2022)
This research departs from the complete learning system of the Yellow Book that exists at the Ibnu Amin Pamangkih Islamic Boarding School. Therefore, this study aims to determine the complete learning of the Yellow Book at the Pondok Pesantren Ibnu Amin Pamangkih in terms of methods and evaluations. This type of research is field research and the approach used is a qualitative approach. The subjects of this study were 5 clerics of the Ibnu Amin Pamangkih Islamic Boarding School and 1 alumni of the Ibnu Amin Pamangkih Islamic Boarding School. The object of this research is the complete study of the Yellow Book at the Pondok Pesantren Ibnu Amin Pamangkih, a review of methods and evaluation. Data collection techniques were carried out by means of interviews, observations and documentaries. The data processing technique uses data reduction, data display and data verification. The research analysis uses descriptive qualitative analysis. The results of this study indicate that 1) The learning methods used are the rote method, the sorogan method, the wetonan/bandongan method, the mudzakarah/bahsul masail method, the question and answer method, the peer tutor method, the i'rab sentence method and the exemplary method. 2) Evaluation of student learning outcomes is carried out thoroughly and continuously, in measuring learning abilities that include all aspects of ability in an integrated manner by checking the ability to read, memorize and explain the content of a book. The students have been tested not only for mastery of knowledge (cognitive) but also reading, listening, explaining (psychomotor) skills and at the same time evaluating the attitude of students towards science (affective).